Spinal cordectomy for the management of thoracic malignant intraspinal tumors in paraplegic or irreversibly, severely paraparetic patients: A technical remark. (October 2019) - Raco, Antonino; Polli, Filippo Maria; Palmieri, Mauro; Cimatti, Marco; Miscusi, Massimo; Frati, Alessandro; Pesce, Alessandro
Highlights: High grade primary spinal neoplasms cause a fatal local progression. High grade primary spinal neoplasms cause a fatal neuraxis diffusion. Spinal Cordectomy was seldom reported but never codified. Spinal Cordectomy is a last chance treatment in paraplegic patients. Step-by-step technique was described in the paper. Abstract: Background: Malignant Intramedullary Spinal Cord Tumor are a relatively uncommon entity affecting patients whose prognosis is quickly and relentlessly dismal. Since the '50s Spinal Cordectomy' has been advocated for the surgical management of these conditions, but to date, no standard operative protocol has been reported yet. Objective: Although apparently "easy", burdened by virtually no further risk for the neurological function in paraplegic or severely paraparetic patients, SCt conceals notable pitfalls and surgical problems that are to date not yet completely discussed. The objective of the present paper is therefore to report a detailed stepwise description of the surgical technique. Methods and results: SCt addresses the problem of reaching a surgical radicality in patients whom neurological preoperative conditions have already irreversibly declined to a deep nonfunctional motor impairment and whose preoperative Brain MRI scan rules out intracranial seeding. The dural sac along with the radicular pouches must be considered as possible seeding and recurrence locations therefore such structure should be "en-bloc" removed. The cranial medullary end of the resection should be identified on the ground of the preoperative MRI and intraoperatively confirmed with fresh histological examinations ruling out the presence of tumor cells above the cordectomy. Due to the topographic and functional medullary arterial anatomy, no SCt should be performed above T3. The risk of postoperative sagittal imbalance is high and therefore a concurrent posterior vertebral stabilization is required. Conclusion: Spinal Cordectomy is a safe and feasible " last chance " treatment to prolong survival in paraplegic or severely paraparetic patients.